‘It is a difficult topic’ – a qualitative study of midwives´ experiences with routine antenatal enquiry for intimate partner violence - Henriksen, L. (BMC Pregnancy Childbirth, 2017)
BACKGROUND: Intimate partner violence (IPV) during pregnancy may jeopardize maternal and fetal health (IJFWM 49:159-164, 2004; IJGO 133:269-276, 2016). In recognition of the significant public health impact of IPV, the Norwegian Directorate of Health issued new guidelines in 2014, which recommend that health professionals routinely ask all women in antenatal care about their exposure to violence. The objective of this study was to gain an in-depth understanding of midwives’ experiences with routine enquiry for intimate partner violence during the antenatal period. METHODS: The study had a qualitative design. Individual semi-structured interviews with eight midwives providing antenatal care at eight Mother and Child Health Centres (MCHC) in Norway were conducted. Graneheim and Lundmans method of content analysis inspired the analysis. RESULTS: Three main themes emerged: Midwives do ask about violence; It can be a challenge; and Factors that make it easier to ask. All midwives enquired, but not on a regular basis, about violence. The midwives’ personal interest in the topic was an important factor that made it easier for them to ask about violence. Lack of time, fear of not knowing how to deal with a positive answer and lack of organizational support were barriers to asking pregnant women about their experiences of violence. CONCLUSION: Midwives were aware of the guidelines and made some efforts to implement them. However, further education and organisational support is needed to enable midwives to routinely ask all pregnant women about IVP. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12884-017-1352-2) contains supplementary material, which is available to authorized users.